Proton pump inhibitor ilaprazole suppresses cancer growth by targeting T-cell-originated protein kinase - Zheng, Mengzhu (Oncotarget, 2017)
T-cell-originated protein kinase (TOPK) is highly and frequently expressed in various cancer tissues and plays an indispensable role in the mitosis of cancer cells, and therefore, it is an important target for drug treatment of tumor. Ilaprazole was identified to be a potent TOPK inhibitor. The data indicated that ilaprazole inhibited TOPK activities with high affinity and selectivity. In vitro studies showed that ilaprazole inhibited TOPK activities in HCT116, ES-2, A549, SW1990 cancer cells. Moreover, knockdown of TOPK in these cells decreased their sensitivities to ilaprazole. Results of an in vivo study demonstrated that gavage of ilaprazole in HCT116 colon tumor-bearing mice effectively suppressed cancer growth. The TOPK downstream signaling molecule phospho-histone H3 in tumor tissues was also decreased after ilaprazole treatment. Our results suggested that ilaprazole inhibited the cancer growth by targeting TOPK both in vitro and in vivo.